Assessment of health-related quality of life in Turkish patients with facial prostheses - ATAY, Arzu; Peker, Kadriye; GUNAY, Yumushan; EBRINC, Servet; Karayazgan, Banu; Uysal, Omer; UYSAL, ÖMER (My University, 2013)
Background: Facial prostheses are intended to provide a non-operative rehabilitation for patients with acquired facial defects. By improving aesthetics and quality of life (QOL), this treatment involves reintegration of the patient into family and social life. The aim of this study was to evaluate the perception of QOL in adult patients with facial prostheses and to compare this perception with that of a control group.
Keywords: facial prostheses